Cimetidine for recurrent ulcer after vagotomy or gastrectomy: a randomised controlled trial. Issue 6122 (13th May 1978) - Kennedy, T; Spencer, A
Abstract : In a randomised controlled trial cimetidine 1 g daily for six weeks was compared with placebo in the treatment of recurrent ulcers after gastrectomy or vagotomy for duodenal ulcer. Healing, assessed endoscopically, was seen in seven out of 12 patients given cimetidine and in five out of 12 controls. Four of the controls whose ulcers did not heal were subsequently treated with cimetidine, and in two the ulcers healed after six weeks. Pain recorded by the patient and consumption of alkalis were each slightly but not significantly less in the cimetidine-treated patients. When cimetidine is to be used for recurrent ulceration probably the dosage and duration of treatment should be increased.